Development of an Automatic Clothesline System Based on Weather Sensors and Telegram Notification - Hanifan Budi Kustiawan; Heri Sudibyo; Dwi Winarti (Komunitas Dosen Indonesia, 2025)
Unpredictable weather conditions often cause outdoor laundry to become wet again, requiring constant manual monitoring. This study presents the design and development of an Internet of Things (IoT)-based automatic clothes drying system that responds to real-time environmental changes and offers remote control via the Telegram application. The system employs an ESP32 microcontroller integrated with a rain sensor, a DHT22 humidity sensor, and an LDR light sensor. Sensor data is processed in real time using predefined threshold values: when rain is detected, humidity exceeds 26%, or light intensity rises above 3500 lux, the ESP32 triggers a servo motor to retract the clothesline. Conversely, in dry and bright conditions (humidity < 25%, light < 3400 lux), the system extends the clothesline. A servo motor is used as the actuator to retract or extend the drying rack. A Telegram Bot is also integrated to deliver real-time notifications and accept manual commands such as /masuk, /keluar, and /status. The development method follows a prototyping approach that includes requirement analysis, hardware-software integration, and system evaluation. Experimental results show that the system achieved over 95% accuracy in detecting environmental changes and responded within 2–3 seconds to commands and sensor triggers. The combination of sensor automation and interactive Telegram control demonstrates reliability and flexibility in smart-home applications. In conclusion, the proposed system provides an effective and user-friendly solution for managing outdoor laundry in variable weather conditions, with promising potential for future enhancements in IoT-based household automation.